EFFECT OF THERMOCYCLING ON FLEXURAL AND IMPACT STRENGTH OF POLYMETHYL METHACRYLATE AND POLYETHERETHERKETONE DENTURE BASE MATERIAL - PUTRA, KRISWANDY; NASUTION, ISMET DANIAL; NASUTION, MUHAMMAD INDRA; ARIYANI; SRIJUNBARL, ANUCHARTE (International Journal of Applied Pharmaceutics, 2025)
Objective: The most widely used resin as denture base is Polymethyl Methacrylate (PMMA). But due to its low impact and flexural strength, it increases the risk of failure during clinical use. To lower the risk of denture base fracture in PMMA full denture, reinforcement material is used. Nowadays, Polyetheretherketone (PEEK) has been introduced in dentistry with better mechanical and physical properties than PMMA. However, there has been no study looking at the effect of aging on the flexural strength and impact of PEEK as a denture base material. Methods: A total of 42 samples consisting of 21 PMMA samples and 21 PEEK samples were made for each Flexural and impact test. The samples were divided into three groups: control, 2000 and 5000 thermocycling cycles, with each group have 7 samples. Flexural strength testing was carried out using the three-point bending method with a universal testing machine while the impact strength test was carried out by the charpy method using a charpy impact testing machine. Results: There was a significant difference in flexural strength between PMMA and PEEK based on the duration of use with a value of p<0.05. There was also a significant difference in he impact strength between PMMA and PEEK based on the length of use with a value of p<0.05. In PMMA group testing on the flexural strength and Impact of PMMA, there was a significant effect with p<0.05. In PEEK group testing on the flexural strength and impact strength, there was no significant effect on the duration of use with p>0.05. Conclusion: PEEK can be used as a base material for dentures that aim to increase flexural and impact strength in the required clinical conditions. There was no significant effect on PEEK mechanical properties in 5 y of use.